Navigating the Journey of Self: A Systematic Review of Gender Identity Formation in Transgender and GenderDiverse Adults from a Global Literature - Iqra, Fiaz; Sana, Rehman; Siti Raudzah, Ghazali; Sadia, Saleem; Shoaib, Abbas (Springer Nature, 2025)
This study presents a multidimensional framework for understanding gender identity development among transgender and gender-diverse (TGD) adults, integrating personal, social, and cultural-contextual factors into a cohesive model. Building upon Lev’s transgender emergence theory and Sevelius’s gender affirmation framework, we analyzed qualitative data from 15 studies (N = 461 participants). The articiles have been taken from diverse databasis such as PsycINFO, PubMed, Scopus, Google Scholar, Psych ARTICLES, Science Direct, JSTOR and the screening has been followed though PRISMA Flow Chart. The quality of the selected qualitative research studies was evaluated using the Critical Appraisal Skills Programme (CASP) quality evaluation instrument. Findings reveal that gender identity development depends upon three interdependent dimensions: (1) personal dynamics (internal processes of recognition, body-mind dissonance, and identity negotiation), (2) social dynamics (community belonging and stigma management), and (3) cultural-contextual influences (structural barriers and intersectional positionality). The results underscore the agenetic role of individuals in navigating their gender identities while also highlighting how systematic inequalities and intersectional marginalization shape divergent developmental trajectories. This review advances the field by proposing the expansion of linear, stage-based models to reflect the complex nonlinear and contextually embedded nature of TJD identity development.